An analysis on common syntactical errors in an Arabic speech discourse: a case study in International Islamic University Malaysia - Yani, Achmad; Suliman Ahmed, Ibrahim; Sahrir, Muhammad Sabri; Muritala, Yahya Toyin; Kama, Nonglaksana (David Publishing, 2014)
The aim of this paper is to investigate the causes of errors which hinder the development of the students of Arabic for the international communication undergraduate programme while applying the syntactical rules of Arabic language during their practical persuasive speech course. The respondents were purposively selected from 23 students who were taking this practical course in an academic semester in their first year of study. The data were collected from students’ presentation and the analysis of the speech discourse was conducted during the second semester of the academic year 2013-2014. The students were requested to present a group presentation on a certain topic by creating a video project via Youtube®, which consists of their speech practical discourse. The findings revealed that the major errors occurred in the application of inflectional parsing during the speech for persuasion among the first year students. In general, the data from the mean analysis revealed that the major errors occurred in the application of inflectional parsing during the speech for persuasion among the students. Based on the syntactical analysis from observation, the researchers found that the most frequent errors were inflectional parsing (22.07%), followed by the least mistake, which was the omission of “Fa” after the word “Ammaa” (1.5%). Other mistakes were found in using the gender of Arabic words (20.7%); singular, dual, or plural forms (19.4%); particles (13.5%); definite article “Al” (12.9%); relative nouns (5.1%); and the use of “an” of gerund after imperfect verb (2.5%). In general, this paper has contributed to a list of syntactical topics that need to be emphasized by teachers in a speech and persuasion course in order to produce quality students for Arabic communication after graduation and to fulfil the needs of market workplace based on descriptive findings and a checklist of observation in persuasive speech.